2008
DOI: 10.1111/j.1365-313x.2008.03510.x
|View full text |Cite
|
Sign up to set email alerts
|

The AtGenExpress hormone and chemical treatment data set: experimental design, data evaluation, model data analysis and data access

Abstract: SummaryWe analyzed global gene expression in Arabidopsis in response to various hormones and in related experiments as part of the AtGenExpress project. The experimental agents included seven basic phytohormones (auxin, cytokinin, gibberellin, brassinosteroid, abscisic acid, jasmonate and ethylene) and their inhibitors. In addition, gene expression was investigated in hormone-related mutants and during seed germination and sulfate starvation. Hormone-inducible genes were identified from the hormone response da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(167 citation statements)
references
References 61 publications
(59 reference statements)
2
156
0
5
Order By: Relevance
“…Other genes have been shown experimentally to be responsive to drought or ABA such as LEA4-1 and OEP16-S (At1g32560 and At4g16160; [33,65]; Additional file 1: Figure S2B and Additional file 1: Figure S1A). The gene pairs were also examined for the extent of co-expression using AtGenExpress Visualisation Tool [38-40] which showed that while in some cases the genes showed very similar patterns of expression, there were also cases where the expression patterns of both genes differed significantly in terms of both temporal and spatial patterns and also in terms of their response to various stresses (Additional file 1: Figure S2). Several parameters can be taken into account when assessing if a gene pairs’ products might be directly linked functionally such as the extent of co-expression and the subcellular co-localization of the gene pair products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other genes have been shown experimentally to be responsive to drought or ABA such as LEA4-1 and OEP16-S (At1g32560 and At4g16160; [33,65]; Additional file 1: Figure S2B and Additional file 1: Figure S1A). The gene pairs were also examined for the extent of co-expression using AtGenExpress Visualisation Tool [38-40] which showed that while in some cases the genes showed very similar patterns of expression, there were also cases where the expression patterns of both genes differed significantly in terms of both temporal and spatial patterns and also in terms of their response to various stresses (Additional file 1: Figure S2). Several parameters can be taken into account when assessing if a gene pairs’ products might be directly linked functionally such as the extent of co-expression and the subcellular co-localization of the gene pair products.…”
Section: Resultsmentioning
confidence: 99%
“…We used the AtGenExpress Visualisation Tool (AVT; http://jsp.weigelworld.org/expviz/expviz.jsp) to extract gene expression data where indicated using the datasets for development, abiotic stress, hormones and light [38-40]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, OPDA-triggered signalling involves activation of TGA transcription factors [64]. The upregulation of PPTE, a reference gene for oxylipin signalling [39], might be the consequence of higher OPDA levels after the H-light transfer. The JA-antagonist SA decreased during N !…”
Section: Discussionmentioning
confidence: 99%
“…Several distinct types of baseline gene expression data exist: tissue, cancer or development profiles (usually absolute expression values), perturbations and diseases (relative values) and time courses and dose responses (absolute or relative values), or a combination of these spatial, temporal and response profiles. Examples of baseline data sets that have been published include the GNF human tissue panel [1], The Cancer Genome Atlas [2], the rat liver and kidney HESI baseline dataset [3], the NOWAC Postgenome Study [4], and the Arabidopsis AtGenExpress datasets for abiotic stress [5], plant development [6], or hormonal and chemical responses [7]. New technological platforms are also frequently assessed by generating data from control samples, resulting in baseline experimental datasets that can subsequently be used as a reference on these platforms.…”
Section: Introductionmentioning
confidence: 99%